Implementasi Pohon Dalam Permainan Aura Kingdom - Destri Herliana Irianti; Fahmi Nova Putera Alfasera (Jurnal Informatika Upgris, 2019)
This paper describes the implementation of trees which is one of the material from discrete mathematics in the game of the Aura Kingdom. In this paper, it is explained about the application and decision making of trees in the game of the Aura Kingdom. Like in choosing a hero, skill information, and weapon mastery.